2018
DOI: 10.1074/jbc.ra118.002447
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of all-trans-retinal into all-trans-retinal dimer reflects an alternative metabolic/antidotal pathway of all-trans-retinal in the retina

Abstract: Free all--retinal (atRAL) and retinal pigment epithelium (RPE) lipofuscin are both considered to play etiological roles in Stargardt disease and age-related macular degeneration. A2E and all--retinal dimer (atRAL-dimer) are two well characterized bisretinoid constituents of RPE lipofuscin. In this study, we found that, after treatment of primary porcine RPE (pRPE) cells with atRAL, atRAL-dimer readily formed and accumulated in a concentration- and time-dependent manner, but A2E was barely detected. Cell-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Cell pellets were extracted as described previously ( 39 ). The resulting extract was dissolved in 100 μl of methanol.…”
Section: Methodsmentioning
confidence: 99%
“…Cell pellets were extracted as described previously ( 39 ). The resulting extract was dissolved in 100 μl of methanol.…”
Section: Methodsmentioning
confidence: 99%
“…It is formed by the reaction of 2 all-trans retinal molecules with phosphatidylethanolamine generating N-retinylidene-PE (A2E precursor: A2-PE), as a detoxication mechanism of retinal isomers including all-trans and 11-cis-retinal [17]. Under normal conditions the ABCA4 protein participates in the elimination of A2-PE from the photoreceptors and inhibition of this clearance increases the accumulation of A2E and all-trans-retinal dimer in the RPE [18,19]. Recently, it has been shown that ABCA4 is also expressed in RPE cells where it would participate in the recycling of retinaldehyde released during proteolysis of rhodopsin in endolysosomes following phagocytosis of photoreceptor outer segments [5].…”
Section: Introductionmentioning
confidence: 99%
“…Primary pRPE cells were prepared as previously reported with slight modifications (Gao et al, 2018). Fresh porcine eyes were dissected under sterile conditions.…”
Section: Methodsmentioning
confidence: 99%